Broadcast Message Authentication Mechanism to Detect Clone and Sybil attacks in VANET’s based on ID-Based Signature Scheme - Shaik, Kareemulla; Ali Hussain, Md. (International Journal of Engineering and Technology, 2018)
Broadcast Communication is crucial in VANET communication, to send and receive safety messages within network. Securing these beacon message is a challenge, since they are very prone to clone and Sybil attacks. Many works have been proposed to address this problem but they failed to address how to detect and protect these messages from clone attacks and also limited to static networks with limited data sizes.Â To achieve this a secure authentication and attack detection mechanism can be designed. In this paper we propose a secure broadcast message authentication and attack detection mechanism with Identity â€“ Based Signatures. Experimental results proved that it can be used in both V2V and V2RSU c communications.Â Â Our scheme shown best performance compared to existing schemes in terms of packet delivery ration, detection rate and detection time.Â Â